Pendampingan Kelompok Guru SMP Al-Bayyinah Makassar dalam Mendesain Pembelajaran Klasifikasi Tumbuhan Berbasis PjBL dan PBL - Faisal Faisal; Hartono Hartono; Asham Bin Jamaluddin; Hamka L; Nur Aisya Ainun (JKM: Jurnal Kemitraan Masyarakat, 2026)
This community service program is motivated by the still-limited competence of teachers in designing innovative, student-centered instruction, particularly in plant classification. Plant classification instruction often remains focused on memorizing concepts and does not provide sufficient opportunities for students to develop critical thinking skills, problem-solving, and scientific inquiry. Therefore, this initiative aims to enhance teachers’ professional and pedagogical competencies through mentoring in designing instruction based on Project-Based Learning (PjBL) and Problem-Based Learning (PBL). The activity was conducted in collaboration with the General and Diniyah Subject Teachers’ Group at Al-Bayyinah Junior High School, Al-Kindi Mas Akbar Foundation, Makassar, through the stages of planning, implementation, mentoring, and evaluation. The methods used included presentations, group discussions, and learning workshops. The results of the activity demonstrated the teachers’ understanding of innovative PBL- and PjBL-based learning. Additionally, participants provided positive feedback on the program's content and activities during implementation. This program is expected to inspire teachers to develop contextual, implementable, and student-centered learning materials on plant classification using PjBL and PBL approaches.